Improved Performance of Titanium Oxide/Silicon Oxide Electron‐Selective Contacts by Implementation of Magnesium Interlayers. Issue 19 (8th August 2021) - Nakagawa, Yuta; Gotoh, Kazuhiro; Inoue, Tetsuya; Kurokawa, Yasuyoshi; Usami, Noritaka
Abstract : The impact of the implementation of magnesium interlayer and the layer thickness ( t TiO x ) of titanium oxide on the electrical properties of TiO x /SiO y /Si heterojunctions is investigated to improve electron transport for use in silicon heterojunction solar cells. The passivation performance is improved with increasing t TiO x . For the samples with Mg interlayer, ohmic contact can be attained for the thicker TiO x layer compared with the sample without Mg interlayer. Schottky contact is mitigated by the TiO x /SiO y stacking layers and Mg interlayer, attributed to the reduction of interfacial energy level by TiO x /SiO y stacking layers and enhanced downward band bending by Mg interlayer. The open‐circuit voltage and fill factor of the solar cells are improved by inserting the TiO x /SiO y stack and the Mg interlayer, indicating that the electron selectivity is enhanced. Excellent surface passivation and transport properties can be achieved by controlling TiO x layer thickness and using the Mg interlayer. Abstract : The impact of the magnesium interlayer on the electrical properties of the TiO x /SiO y heterocontact is investigated to improve the transport properties of the heterostructure. Combining the TiO x /SiO x stack and Mg interlayer results in mitigation of Schottky contact, and thus electron transport is improved.